1992
DOI: 10.2337/diacare.15.12.1902
|View full text |Cite
|
Sign up to set email alerts
|

Complications: Neuropathy, Pathogenetic Considerations

Abstract: The most common form of neuropathy associated with diabetes mellitus is distal symmetric sensorimotor polyneuropathy, often accompanied by autonomic neuropathy. This disorder is characterized by striking atrophy and loss of myelinated and unmyelinated fibers accompanied by Wallerian degeneration, segmental, and paranodal demyelination and blunted nerve fiber regeneration. In both humans and laboratory animals, this progressive nerve fiber damage and loss parallels the degree and/or duration of hyperglycemia. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
159
1
7

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(171 citation statements)
references
References 66 publications
4
159
1
7
Order By: Relevance
“…Other studies found autonomic neuropathy in newly diagnosed type 2 diabetic subjects (36,37). It has generally been accepted that neuropathy is a consequence of long-term hyperglycemia (38,39), and studies have shown that dysregulation of diabetes affects the progression of autonomic neuropathy in a negative way (40,41). In our study, long-term hyperglycemia is not a plausible cause of autonomic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found autonomic neuropathy in newly diagnosed type 2 diabetic subjects (36,37). It has generally been accepted that neuropathy is a consequence of long-term hyperglycemia (38,39), and studies have shown that dysregulation of diabetes affects the progression of autonomic neuropathy in a negative way (40,41). In our study, long-term hyperglycemia is not a plausible cause of autonomic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The polyol pathway is thought to play a major metabolic role in the development of diabetic neuropathy (Greene & Sima, 1992;Sima & Sugimoto, 1999;Zochodne, 1999;Vinik, Pittenger, McNitt, & Stansberry, 2000). Persistent hyperglycemia increases the polyol pathway activity in conjunction with accumulation of sorbitol and fructose in nerves, and this is accompanied by a reduction in myo-inositol uptake and inhibition of Na + /K + -ATPase, resulting in Na + retention, edema, myelin swelling, axoglial disjunction, and nerve degeneration (Greene, Lattimer, & Sima, 1987;Vinik, Pittenger, McNitt, & Stansberry, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…All these observations have collectively given rise to the sorbitol theory of diabetic neuropathy, linking the changes in inositol and sorbitol content in a mostly chronic diabetic nerve to its functional alterations, e.g., altered phosphoinositide metabolism, Na+ ,K + -ATPase activity, and nerve conduction velocity. AR activation by hyperglycemia has been linked to myo-inositol (MI) depletion, defects in phosphoinositide and Na+ ,K + -ATPase regulation, slowing nerve conduction, and structural defects in diabetic neuropathy (Greene et al, 1992). Experimental diabetes also gives rise to MI depletion, reduced nerve Na + ,K + -ATPase activity, and nerve conduction slowing, which can be prevented by dietary MI supplementation (Greene et a!., 1975(Greene et a!., , 1982Palmano et al, 1977;Greene and Winegrad, 1981;Greene and Lattimer, 1983;Mayer and Tomlinson, 1983).…”
mentioning
confidence: 99%